Association of the functional SNP rs2275294 in ZNF512B with risk of amyotrophic lateral sclerosis and Parkinson's disease in Han Chinese. Issue 1 (17th February 2016) - Yang, Xinglong; Zhao, Quanzhen; An, Ran; Zheng, Jinhua; Tian, Sijia; Xu, Yanming
Abstract : The single nucleotide polymorphism (SNP) rs2275294 of the ZNF512B gene has been reported to be associated with a risk of ALS in the Japanese population. Here we conducted a case-control study examining the possible association of rs2275294 with risk of sporadic ALS and PD in Han Chinese. Our study included 301 patients with ALS and 457 age- and gender-matched controls, as well as 555 patients with PD and 473 age- and gender-matched controls. Subjects were genotyped at rs2275293 using the ligase detection reaction. The genotype distribution of rs2275294 shows significant difference between patients with ALS and the control group according to the dominant model (OR 1.518, 95% CI 1.074–2.145, p = 0.018) and based on alleles (OR 1.249, 95% 1.016–1.534, p = 0.035). Stratification analysis showed a significant difference between females with ALS and female controls based on the dominant model (OR 3.285, 95% CI 1.856–5.815, p < 0.001) or alleles (OR 1.697, 95% CI 1.208–2.383, p = 0.002). In contrast, no significant differences were identified between rs2275294 and patients with PD. In conclusion, our case-control study suggests that the CC genotype and C allele at rs2275294 are associated with increased risk of ALS in Han Chinese, particularly females.